Analisis Penggunaan Aplikasi Pencatatan Keuangan Berdasarkan Teori TAM: (Studi Kasus Pada Online Shop “Sweet Palettee”) - Riza Ahmadina Qawiyyu; Hero Priono (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2024)
This research was conducted to determine the perception and readiness of an online shop to use a financial accounting application based on the Technology Acceptance Model (TAM) theory. Therefore, interpretive qualitative research was carried out using a descriptive case study approach at the online shop